Kesanggupan membayar penambahbaikan taraf perkhidmatan air di Kuala Terengganu - Mahirah Kamaludin,; Kuna Sandran,; A.A. Azlina,; Alias Radam, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The aim of this study was to determine the willingness to pay (WTP) by domestic users in Kuala Terengganu district, in the effort to improve the quality of water services in the future. Water services should be managed resourcefully based on efficient water tariff since any rise in water services would involve high operational costs. The Contingent Valuation Method (CVM) was applied to determine users’ willingness to pay for the newly offered water tariff. In this study, 400 domestic users from the Kuala Terengganu district were involved. The Logit Model was used to analyse the data collected through interviews. The results showed that factors such as new water tariff and household income have a significant relationship with the willingness to pay among users in that district. The willingness to pay for the new water tariff was averaged at RM 0.60 for the first 30 m3, and the new tariff is higher than the current water tariff being offered. New water tariff can be recommended to improve and further develop the water services to a higher level in the future. This effort was initiated to meet user demands that have been increasing each year.